Progress and challenges in numerically modelling solid sports balls with application to softballs - Smith, L. V.; Duris, J. G. (Journal of Sports Sciences, 2009)
Much of the work surrounding finite element simulation of bat-ball impacts has focused on techniques describing the ball. Determining the accuracy of these models has been hindered by challenges in experimentally characterizing the ball's response. In the following, dynamic mechanical analysis and an instrumented impact test were used to characterize the solid ball at deformation rates representative of play. The ball was described in the numerical model as a linear viscoelastic material. It was observed that a Prony series model based on small deformation dynamic mechanical analysis did not provide sufficient energy loss upon impact, while a simpler Power Law model, fitted to large deformation data, described the measured energy loss and impact force over a range of speeds. Results of a parametric study are presented as a guide towards tailoring the parameters of the Power Law model to match the measured energy loss and impact force. Discrepancies observed between the experiment and the numerical model suggest that the ball response should be characterized in environments closely resembling game conditions.